Ситуативная и личностная тревожность студента в эргатической компьютерной обучающей системе - Страхова, О. П. (ТДМУ, Київ, 2015)
The work in ergatic learning system may have an influence into the human functional state changes. The quantitative parameters of such changes may be detected by measuring the electrocutaneous characteristics in the special control acupuncture points on the human limbs - so-called microzones. To study the interconnections between situational and personal anxiety of a human and his electrocutaneous parameters, the present research was implemented. It was established that these parameters have changes according to the individual’s character.
Student’s situational and personal anxiety in ergatic learning system
Keywords: ергатична навчальна система; шкала Спілбергера; електрошкірні характеристики; ситуаційна тривожність